ON COPRIMARY MODULES - Al-Omairy, Layla Hashem Helal (Al-Nahrain Journal of Science, 2010)
Let R be commutative ring with identity. In this paper, we give the dual of the concept primarymodules which is called coprimary modules with some properties Also the concept of carationalmodules with some properties is given.